A double-blind, placebo-controlled trial of the efficacy and safety of two doses of azelastine hydrochloride in perennial allergic rhinitis - Bousquet, Jean; Klimek, Ludger; Kuhl, Hans-Christian; Nguyen, Duc Tung; Ramalingam, Rajesh Kumar; Canonica, G. W.; Berger, William E. (Frontiers in Allergy, 2023)
Background: Azelastine hydrochloride (AZE) is a selective, non-sedating H1-antagonist with anti-inflammatory, and mast cell stabilizing properties which can be used as an alternative to intranasal corticosteroids. The objective of this study was to evaluate the efficacy of the new formulation of 0.15% AZE compared to placebo at a dosage of two sprays per nostril twice daily over 4 weeks in subjects with perennial allergic rhinitis (PAR). Materials and Methods: A total 581 subjects were randomized in this double-blind, placebocontrolled trial (NCT00712920) that compared AZE 0.10% (1096 mcg daily) and 0.15% (1644 mcg daily) to placebo in PAR patients. The study consisted of a 7-day, single-blind placebo lead-in period and a 28-day, DB treatment period. The primary end point was the change from baseline in 12-hour reflective Total Nasal Symptom Score (TNSS) for the entire 28-day study period of 0.15% AZE 2 sprays per nostril BID compared to placebo. The efficacy and safety of 0.15% AZE was compared to placebo. Results: LS mean improvement from baseline in the AM and PM combined rTNSS was statistically significant for 0.15% AZE (p=0.04) when compared to the placebo group. LS mean improvement from baseline in the AM and PM combined rTNSS was 4.10 (4.26) units for 0.15% AZE and 3.81 (3.99) for 0.10% AZE. For individual symptoms, there was a statistically significant change in the LS mean (p=0.04) change from baseline in the 12-hour reflective assessment in the 0.15% AZE group for runny nose. Further numerical improvements were shown for itchy nose, nasal congestion, runny nose, sneezing compared to placebo. There were no deaths and no serious adverse events related to the study medication reported.The present formulation 0.15% AZE is safe and effective in relief of PAR symptoms. It effectively relieves nasal as well as non-nasal symptoms.